PENINGKATAN PERKEMBANGAN MOTORIK HALUS MELALUI TEKNIK MOZAIK PADA ANAK USIA 5-6 TAHUN - Salim, Sandora; Syukri, Muhammad; Ali, Muhammad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Â AbstractThe background of this study is children who have difficulty in fine motor skills, among others on the activity of sticking, cutting, matching. The problem in this study is: "Does applying mosaic technique in learning can improve the fine motor development in children aged 5-6 years in Kindergarten Gembala Baik Pontianak?". The purpose of this study is to determine the improvement of fine motor development by applying the mosaic technique in children aged 5-6 Years in Good Shepherd Kindergarten Pontianak. This form of research is a classroom action research.Based on the results of research that has been done and through the results obtained after the data analysis, generally drawn conclusions Learning planning to improve fine motor in children aged 5-6 years is categorized "very good", Implementation of learning using mosaic techniques in improving the fine motor skills of children aged 5-6 years has been categorized very well, and Improved fine motor skills by using mosaic techniques in children aged 5-6 years can be categorized very well developed in this case the child is neatly attached, clean in the paste and have the appropriate pattern.Keywords: Fine Motor, Mosaic